Recent Referees (Journal of Political Economy, 2019)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Richard AkreshS. Nageeb AliFranklin AllenSiwan AndersonIsaiah AndrewsJose ApesteguiaAndrew AtkesonHeski Bar-IsaacPhilip BarrettBrian BeachJonathan BeauchampDaniel BenjaminRaquel BernalDan BernhardtV BhaskarAnna BindlerAndreas BlumeAlessandro BonattiOzan CandoganTimothy CasonDavid CesariniChristopher ChambersDamon ClarkAlain CohnJanet CurrieXianchi DaiErnesto Dal BoRafael Di TellaWill DobbieUlrich DoraszelskiMartin DufwenbergKeith EricsonSelman ErolJason FabermanJames FearonRaymond FismanChristopher FlinnAnthony FowlerXavier GabaixSebastian GalianiYana GallenPeter GanongRonald GoettlerRussell GolmanBenjamin GolubGautam GowrisankaranJeff GroggerGene GrossmanLars HansenTerrence HendershottHolger HerzRandi HjalmarssonMitchell HoffmanRichard HoldenRichard HornbeckPatrick HummelMitsuru IgamiLakshmi IyerPamela JakielaSeema JayachandranRobert JensenIan JewittLouis KaplowMichael KatzRalph KoijenFuhito KojimaAnton KolotilinSerhiy KozakAlbert KyleJoanna LaheyRasmus LandersoeFabian LangeAudrey LaporteBrad LarsenJohn LeahySangMok LeeLars LefgrenArik LevinsonShengwu LiAnnie LiangIlse LindenlaubMatthew LindquistBenjamin LockwoodLee LockwoodAlexander MackayJames MalcomsonMarco MariottiPaco MartorellGiovanni MastrobuoniR. McAfeeRyan McDevittXin MengRobert MoffittBenny MoldovanuFrancesca MolinariJack MountjoySharun MukandRichard MurphyDavid NeumarkPaul NiehausSam NorrisEmily OsterMichaela PagelAmanda PallaisLubos PastorAlessandro PavanJacopo PeregoRicardo Perez-TrugliaPetra PerssonRobert PollakJoseph PriceNancy QianNatalia RamondoChris RobinsonJames RobinsonGuillaume RocheteauAnne-Katrin RoeslerWilliam RogersonAdam RosenNilanjan RoyAldo RustichiniMartin SaavedraJohn SabelhausBernard SalanieTobias SalzAndres SantosAndrew SchotterEmanuela SciubbaEdson SeverniniDaniel SilvermanOskar SkansIsaac SorkinCharles SprengerYves SprumontBruno StruloviciMatthias SutterAlexander TabarrokMathieu Taschereau-DumouchelAlan TaylorMelissa ThomassonChristopher TimminsMirco ToninEric Van WincoopJoseph VavraEmanuel VespaSofia Villas-BoasReed WalkerTodd WalkerChristopher WallaceEbonya WashingtonDavid WettsteinDavid WheelockHeidi WilliamsEdward WolffThomas WollmannLeeat YarivNoam YuchtmanJohn Yiran ZhuOwen ZidarJames Ziliak Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 4August 2019 Article DOIhttps://doi.org/10.1086/705558 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.